2010
DOI: 10.1007/s12031-010-9421-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Semax and Its C-End Peptide PGP on the Morphology and Proliferative Activity of Rat Brain Cells During Experimental Ischemia: A Pilot Study

Abstract: The neuropeptide preparation Semax (Met-Glu-His-Phe-Pro-Gly-Pro) has been employed successfully in clinical practice for treating patients with severe brain blood circulation disorders. In spite of numerous studies, many aspects of the therapeutic effects of this preparation remain unknown. In this context, the effects of Semax and its C-end tripeptide PGP on the functional morphology of nervous tissue cells were studied in the normal rat brain and in a model of incomplete global rat brain ischemia. In control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Three hours after occlusion, Semax altered the expression of genes associated with the artery vasodilation process as well. Our earlier studies showed that capillary bore extension was observed as early as 15 min after the administration of the peptide [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three hours after occlusion, Semax altered the expression of genes associated with the artery vasodilation process as well. Our earlier studies showed that capillary bore extension was observed as early as 15 min after the administration of the peptide [9]. …”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown the effect of Semax on the expression of genes that encode neurotrophic factors and their receptors in an experimental model ischemia in the rat brain [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the expression of the nuclear protein PCNA, which participates in the preparation for cell division, was also noted. Judging by the upregulation of PCNA in the nuclei of the brain cells of control animals, Semax appears to stimulate the proliferation of repopulating elements of the nervous tissue [73].…”
Section: Neurotrophic Effectmentioning
confidence: 98%
“…Пептид семакс (Met-Glu-His-Pro-Gly-Pro), синтезований в Інституті молекулярної генетики РАН, є нейроактивним аналогом адренокортикотропного гормону (АКТГ), який має низку нейропротекторних властивостей. У ЦНС він сприяє підвищенню рівня проліферації нейроглії і ендотелію кровоносних капілярів, а також поліпшенню стану нервової тканини при ішемії [1]. Семакс широко використовується при лікуванні алергічних і запальних захворювань зорового нерва [2], позитивно впливає на розвиток пам'яті, навчання і уваги.…”
Section: вступunclassified